Ultrasound-enhanced fine-needle biopsy improves tissue yield in head and neck tumors ex vivo - Minna Rehell; Yohann Le Bourlout; Jetta Kelppe; Jaana Rautava; Emanuele Perra; Jouni Rantanen; Gösta Ehnholm; Nick Hayward; Kristofer Nyman; Kenneth P. H. Pritzker; Jussi Tarkkanen; Timo Atula; et al. (Scientific Reports)
Abstract Current needle biopsy techniques, i.e., fine-needle aspiration biopsy (FNAB) and core needle biopsy (CNB), are widely utilized in cancer diagnostics but have certain shortcomings. The limited yield of diagnostic cellular material and the low sensitivity to detect various types of malignancies are well-known problems with FNAB. In contrast, CNB provides a histological sample but is typically more labor-intensive to obtain. Ultrasound-enhanced FNAB (USeFNAB) represents a novel approach that utilizes an ultrasonically oscillating fine-needle tip to enhance tissue yield. This study aims to assess the feasibility of employing USeFNAB in head and neck tumors in an ex vivo setting. Parotid gland tumors (PGT; N = 10) and neck lymph nodes of patients with head and neck cancer (HNC; N = 10) were resected and biopsied using three techniques: USeFNAB, FNAB, and CNB which served as a comparative method. The samples obtained were weighed and the yield and quality of the tissue fragments were evaluated by pathologists. Immunohistochemical staining was performed to determine whether USeFNAB had any impact on the staining characteristics of the sample. The findings showed that USeFNAB, at a 0.5 W power level, produced a tissue sample (mass) that was 1.9 times higher in the PGT group, and 4.6 times higher in the HNC group compared to FNAB. The quality of the sample obtained via USeFNAB was comparable to that of FNAB. USeFNAB did not alter the immunohistochemical staining characteristics. Overall, USeFNAB appears to be a promising tool for improving the tissue yield of fine-needle biopsy and enhancing diagnostic accuracy.